Acute thrombosis of an atrial flow regulator in a failing Fontan circulation: recanalization and management - Raymond N. Haddad; Ahmed Adel Hassan; Mahmoud Al Soufi; Mohamed Kasem (BMC Cardiovascular Disorders)
Abstract We report the case of an 11-year-old boy with situs inversus, interrupted inferior vena cava with azygos continuation, persistent left superior vena cava with absent bridging vein, congenitally corrected transposition of the great arteries, pulmonary atresia, and ventricular septal defect. He underwent a Kawashima shunt at age 1 and fenestrated extracardiac conduit Fontan completion at age 9, delayed due to loss to follow-up while living abroad. Fifteen months post-op, the patient was diagnosed with plastic bronchitis. Cardiac catheterization revealed elevated Fontan pressures and proximal left pulmonary artery stenosis, which was stented (AndraTec 38 mm Optimus-XL). Although fenestration creation was considered, the procedure was initially delayed allowing for a trial of medical management. Four months later, a 6 mm Occlutech atrial flow regulator (AFR) was placed transjugularly, but thrombosis occurred 48 h later. Transjugular catheter-based clot aspiration (Penumbra Lightning® 7) and stenting (10/20 mm Cook Formula stent) followed by sequential high-pressure ballooning increased the fenestration diameter, improving symptoms and hemodynamics. He had a favorable recovery with significant improvements and remained stable at 13 weeks of follow-up.